Pengaruh Model Pembelajaran ARCS (Attention, Relevance, Confidence, Satisfaction.) dan Motivasi Terhadap Hasil Belajar IPS Siswa Kelas V SD Negeri 75 Kota Bengkulu - Sukarno Sukarno; Salamah Salamah (At-Ta'lim : Media Informasi Pendidikan Islam, 2019)
Abstract: Effect of ARCS Learning Model (Attention, Relevance, Confidence, Satisfaction) and Motivation on Social Studies Learning Outcomes of 5th Grade Students 75th State Elementary in Bengkulu City. This study aimed to determine the differences in student learning outcomes using the ARCS learning model with conventional learning models in class V of SD Negeri 75 Kota Bengkulu, differences in learning outcomes from groups of students with high learning motivation levels using the ARCS learning model with conventional learning models in class V SD Negeri 75 Kota Bengkulu, differences in learning outcomes from groups of students with low learning motivation levels using the ARCS learning model with conventional learning models in class V of SD Negeri 75 Kota Bengkulu, and interaction of learning models with motivation towards learning outcomes of fifth grade students at SD Negeri Kota Bengkulu. This study uses a quantitative approach with a type of quasi-experimental research. The subjects of this study were 75 elementary school students in the city of Bengkulu, totaling 62 students. Data collection is done by using tests and questionnaires with a research design using factorial 2X2. Data analysis techniques, using the "t" test and "F" test The results showed 1) Overall there are differences between student learning outcomes taught by using the ARCS learning model with conventional learning models IPS subjects class V SD Negeri Bengkulu city. By showing the test results "t" Sig. 0,000 (2-tailed) <0.050. 2) there are differences in learning outcomes of students with high learning motivation between those taught by using the ARCS learning model with conventional learning models on social studies subjects in class V of SD Negeri 75 Kota Bengkulu. By showing the results of the "t" test sig value of 0.010 <alpha 5% (0.050). 3) there is no difference in learning outcomes of students with low learning motivation between those taught by using the ARCS learning model with conventional learning models on social studies subjects in class V 75 SD Negeri Bengkulu city. With the results of the "t" test, the sig value is 0.235> alpha 5% (0.050). 4) There is no interaction between the learning model and learning motivation towards student learning outcomes in social studies subjects in grade V in SD Negeri 75 Kota Bengkulu. By showing the results of the "F" test sig. 0.490> 0.050 .Abstrak: Pengaruh Model Pembelajaran ARCS (Attention, Relevance, Confidence, Satisfaction) dan Motivasi Terhadap Hasil Belajar IPS Siswa Kelas V  SD Negeri 75 Kota Bengkulu. Penelitian ini bertujuan Untuk mengetahui perbedaan hasil belajar siswa dengan menggunakan model pembelajaran ARCS dengan model pembelajaran konvensional pada kelas V SD Negeri 75   Kota Bengkulu, perbedaan hasil belajar dari kelompok siswa yang tingkat motivasi belajar tinggi dengan menggunakan model pembelajaran ARCS dengan model pembelajaran konvensional pada kelas V SD Negeri 75  Kota Bengkulu, perbedaan hasil belajar dari kelompok siswa yang tingkat motivasi belajar rendah dengan menggunakan model pembelajaran ARCS dengan model pembelajaran konvensional pada kelas V SD Negeri 75  Kota Bengkulu, dan interaksi model pembelajaran dengan motivasi terhadap hasil belajar siswa kelas V SD Negeri Kota Bengkulu. Penelitian ini menggunakan pendekatan Kuantitatif dengan jenis penelitian quasi eksperimen . Subjek penelitian ini adalah siswa SD Negeri 75 kota Bengkulu  yang berjumlah 62 orang siswa. Pengumpulan data dilakukan dengan menggunakan tes dan angket dengan desain penelitian menggunakan factorial 2X2.  Teknik analisis data, menggunakan uji “t” dan uji “F” Hasil penelitian menunjukkan 1) Secara keseluruhan terdapat perbedaan hasil belajar siswa antara yang diajar dengan menggunakan model pembelajaran ARCS dengan model pembelajaran konvensional mata pelajaran IPS kelas V SD Negeri kota Bengkulu. Dengan ditunjukkan hasil uji “t” Nilai Sig.  0,000 (2-tailed) < 0.050. 2) terdapat perbedaan hasil belajar siswa dengan motivasi belajar tinggi antara yang diajar dengan menggunakan model pembelajaran ARCS dengan model pembelajaran konvensional pada mata pelajaran IPS kelas V SD Negeri 75 kota Bengkulu. Dengan ditunjukkan hasil uji “t” Nilai sig sebesar 0.010 <  alpha  5%  (0,050). 3) tidak terdapat perbedaan hasil belajar siswa dengan motivasi belajar rendah antara yang diajar dengan menggunakan model pembelajaran ARCS dengan model pembelajaran konvensional pada mata pelajaran IPS kelas V SD Negeri 75 kota Bengkulu. Dengan ditunjukkan hasil uji “t” Nilai sig sebesar 0.235 > alpha  5%  (0,050). 4) Tidak terdapat interaksi antara model pembelajaran dengan motivasi belajar terhadap hasil belajar siswa pada mata pelajaran IPS kelas V  SD Negeri 75 kota Bengkulu.  Dengan ditunjukkan hasil uji “F” sig. 0.490 > 0.050.